CANONICAL CORRELATION BETWEEN BASIC-MOTOR ABILITIES AND KARATE COMPETITOR’S EFFICACY - Branimir Mikić,; Džemal Huremović,; Jasmin Mehinović,; Sylejman Shala, (Sport Scientific And Practical Aspects, 2025)
The main characteristic of karate is conflict of two fighters in a certain space with certain rules of behavior with constant supervision of judges. Complex phenomenon of karate requires discipline and scientific approach of all its aspects. The research was conducted on the sample of 61 respondents – top class karate players in order to determine canonical correlation between basic-motor abilities and competitor’s efficacy. With canonical analysis we extracted one significant canonical factor. Analyzing variable projections through extracted canonical factor, we can conclude competition efficacy depends on arms and legs movement speed, segmented speed of arms and explosive strength of lower extremities.